Education for Sustainable Development (ESD): Analysis of System Thinking Competencies of Primary School Learners - Mia Azzahra; Pramudiyanti Pramudiyanti; Fatkhur Rohman; Muhammad Nurwahidin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Sustainable Development Goals (SDGs) is a 2030 agenda comprised of 17 goals. One of these goals, the fourth, pertains to Quality Education and includes indicator 4.7, Education for Sustainable Development (ESD), as one of its achievements. The implementation of ESD in education targets the instillation of systems thinking competencies within learning objectives. Consequently, students are expected to possess systems thinking competencies as a direct outcome of the learning process. The purpose of the research is to find out how good the system thinking competence of students in elementary schools is. Method: This study employs descriptive quantitative methods, analyzing 15 tested items to assess system thinking competencies. The analysis of competency in system thinking involved 65 sixth-grade students at Elementary School 1 Sukaraja. Data collected was analyzed using the Rasch model via the Winstep application. Results: The analysis of the data obtained revealed a notably low interaction between the items and the student's responses, with Cronbach Alpha producing a logit of 0.34. This suggests that students have limited ability to engage with complex systems, as evidenced by the logit number of -0.8. Novelty: The development of systems thinking competency in elementary school students must be continually monitored and fostered as an essential aspect of applying ESD principles to real-life issues to ensure a sustainable future. This is based on an analysis of the data obtained regarding the long-term impact of such an approach on the students' problem-solving abilities.